2017
DOI: 10.15406/ijcam.2017.07.00215
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Potential of Terpenes from Spondias Purpurea L. Leaf Extract against Moniliophthora Perniciosa that causes Witches Broom Disease of Theobroma Cacao

Abstract: The present in vitro study evaluates antifungal properties of Spondias purpurea plant extract against Moniliophthora perniciosa. Fractions of Ethanol Crude Extracts (CE) from S. purpurea were tested for their antifungal activity. CE inhibited mycelial growth of M. perniciosa by 60%at a dose of 10 mg/mL, while survival of broken hyphae of the fungus was inactivated by 90% at a dose of 8 mg/mL. Fractionation of CE yielded a terpene containing sub fraction (FA) with the highest fungicidal activity. FA acted as ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…One investigated the oxidant activity of CE in yeast mutants related to deficiency in oxidative stress (cttΔ, ctaΔ, sod1Δ and sod2Δ). These data corroborate studies found by Marisco et al (2017), who indicates that oxidative activity via free radical production. This study of S. purpurea showed toxicity (FC) when compared to the standards described by Meyer et al (1982).…”
Section: Mic/ic50 (Mg/ml)supporting
confidence: 93%
See 2 more Smart Citations
“…One investigated the oxidant activity of CE in yeast mutants related to deficiency in oxidative stress (cttΔ, ctaΔ, sod1Δ and sod2Δ). These data corroborate studies found by Marisco et al (2017), who indicates that oxidative activity via free radical production. This study of S. purpurea showed toxicity (FC) when compared to the standards described by Meyer et al (1982).…”
Section: Mic/ic50 (Mg/ml)supporting
confidence: 93%
“…The inhibition of cell division observed through the values of the mitotic index in S. purpurea demonstrates that this plant has potential for antiproliferative capacity. This response may be associated with the presence of terpenes detected in phytochemical analysis performed with the extract of S. purpurea (Marisco et al, 2017).…”
Section: Mic/ic50 (Mg/ml)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, plant metabolites are a rich source of bioactive compounds explorable for the use of preventing and controlling plant pathogenic microbes. In the last decade, several studies investigated terpenoids as potential antiphytopathogenic compounds [ 67 , 71 , 76 , 77 , 107 , 108 ]. β-caryophyllene is a natural bicyclic sesquiterpene that is a constituent of many essential oils.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, plants, as a part of a complex ecosystem, can produce enormous amounts of secondary metabolites for their survival and maintenance. Phenolics and terpenes are examples of metabolites that are produced by plants and act as antimicrobial agents and feeding deterrents [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. The presence of a wide range of terpenes encouraged their use as nature-inspired plant protection agents in agriculture or their use for drug development.…”
Section: Introductionmentioning
confidence: 99%